Eco-labels, Production Related Externalities and Trade - Mads Greaker (Statistics Norway, Research Department, 2002)
We analyze the trade and welfare effects of eco-labels in a domestic market with one domestic firm and one foreign firm. Pollution is production related, and the government can choose between including the product category in an eco-label scheme and setting an environmental standard. The environmental standard will only apply to the domestic firm, while both firms can adopt the eco-label. Given that the environmental damage is not too large, we find that it is optimal for the government to introduce an eco-label scheme. An eco-label scheme is optimal even though the domestic firm may loose profit and the foreign firm may gain. Hence, the eco-label scheme is not introduced for protectionist purposes. Further, if the government for some reason were prevented from using eco-labels, global, domestic and foreign welfare would be hampered.
Keywords: H7; Q2; R3; 330; Eco-labels; strategie environmental; policy; trade